Hard Combination Data Fusion for Cooperative Spectrum Sensing in Cognitive Radio - Md. Shamim Hossain; Md. Mahabubur Rahman; Md. Ibrahim Abdullah; Mohammad Alamgir Hossain (International Journal of Electrical and Computer Engineering (IJECE), 2012)
This paper presents a study of hard combination data fusion for cooperative spectrum sensing in Cognitive Radio (CR). We evaluated the performance of cooperative spectrum sensing with the hard combination OR, AND and MAJORITY rules. Energy detection technique is used to sense the presence of primary user (PU) signal. Simulation result shows that cooperative spectrum sensing with OR rule is the best among hard combination data fusion in Cognitive Radio and gives the better performance than AND and MAJORITY rules.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1814